King and Messiah as Son of God: divine, human, and angelic Messianic figures in Biblical and related literature - Collins, Adela Yarbro (Eerdmans, 2008)
The King as Son of God -- The kingship in Deuteronomistic and prophetic literature -- Messiah and Son of God in the Hellenistic period -- Messiah and Son of Man -- Jesus as Messiah and Son of God in the letters of Paul -- Jesus as Messiah and Son of God in the Synoptic Gospels -- Jesus as Son of Man -- Messiah, Son of God, and Son of Man in the Gospel and Revelation of John